Development of MS ISO 9001 : 2008 management system for Automotive Excellence Center (AEC) at University Malaysia Pahang - Amirul Aliff, Jamaludin (2009)
In this thesis, the knowledge of development for MS ISO 9001:2008 Quality Management System is studied theoretically. This study is to establish the quality manual and operation procedures based on clause 1, clause 2, clause 3, clause 4, clause 7 and clause 8 of ISO 9001:2008 quality management system for Automotive Excellence Center (AEC). AEC need to implement MS ISO 9001:2008 Quality Management System since this implementation basically provides a unique framework for AEC to establish a customer satisfaction oriented quality system that is internationally recognised and can be independently assessed and certified. Study was mainly carried out by literature study, discussion with supervisor and preparing the letter go along with visit to International Islamic University Malaysia that already get their certification in MS ISO 9000 Quality Management System. From that visit, there will be surveying process, analysis of the surveying, result and discussion of the implementation of MS ISO 9000 Quality Management System and conclusion. This thesis will note down all the requirements that list in clause 1, clause 2, clause 3, clause 4, clause 7 and clause 8 based on MS ISO 9001:2008 Quality Management System through the establishment of quality manual, operation procedures, work instruction and documentation. This establishment of quality manual and operation procedures hopefully can maximum the staff and AEC efficiency based on knowledge of MS ISO 9001:2008 Quality Management. Hopefully that the result and discussion come out will contributed to Automotive Excellent Center in Universiti Malaysia Pahang to achieve their mission to provide world class research equipment and facilities for automotive research and collaboration with domestic and foreign research institutions and universities for automotive development and knowledge sharing.